Factors affecting the purchase of local beverage product / Noorita Mohammad, Mariam Setapa and Khairunnisa Rahman - Mohammad, Noorita; Setapa, Mariam; Rahman, Khairunnisa (2012)
This study is carried out to measure how far product promotion by advertising of Small and Medium Industries (SMls) could influence the purchase by user. The study focuses on promotion by using advertising of product Small and Medium Industries (SMls). The outcomes of this research are essential to readers in order to understand the dimension that influences consumer to buy product. Furthermore, the research is important to recognize the relationship of the marketing mix which consists of Product, Price, Promotion and Place towards consumer satisfaction and this research focus on promotion by advertising. Quantitative method had been used in this study. The respondent come from 300 of students University Technology MARA, Johor and people around Segamat. The result shows there are significant relationship between promotion by advertising and intention to consumer buying product beverage SMls